Effect of Jigsaw Teaching Strategy on Academic Achievement and Interest in Chemistry among Senior Secondary School Students in Gombe, Gombe State, Nigeria - Mailaya, J. M.; Dalhatu, Aliyu Hassan; Lammaru, R. F; Baba, Usman Sabo (Kashere Journal of Education, 2025)
This study investigates the effects of the Jigsaw Teaching Strategy on academic achievement and interest in chemistry among senior secondary school students in Gombe State, Nigeria. A quasi-experimental design was employed, involving 200 students from two intact classes, randomly assigned to experimental and control groups. The Guttmann Interest Rating Scale (GIRS) was used to assess student interest, while academic achievement was measured via a chemistry achievement test. The data were analysed using Analysis of Covariance (ANCOVA) to test the null hypotheses at a significance level of 0.05. The results showed that students who learned using the Jigsaw strategy did much better on tests than those who learned using traditional methods (F = 328.562, P = .000). Additionally, gender did not significantly influence achievement (F = 524.330, P = .000), indicating that the Jigsaw Teaching Strategy effectively enhanced student outcomes across genders. The study recommends integrating the Jigsaw approach into the curriculum as a means of fostering greater engagement and understanding in chemistry education.